Serial Molecular Profiling of Low-grade Prostate Cancer to Assess Tumor Upgrading: A Longitudinal Cohort Study - Salami, Simpa S. (Eur Urol, 2020)
BACKGROUND: The potential for low-grade (grade group 1 [GG1]) prostate cancer (PCa) to progress to high-grade disease remains unclear. OBJECTIVE: To interrogate the molecular and biological features of low-grade PCa serially over time. DESIGN, SETTING, AND PARTICIPANTS: Nested longitudinal cohort study in an academic active surveillance (AS) program. Men were on AS for GG1 PCa from 2012 to 2017. INTERVENTION: Electronic tracking and resampling of PCa using magnetic resonance imaging/ultrasound fusion biopsy. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: ERG immunohistochemistry (IHC) and targeted DNA/RNA next-generation sequencing were performed on initial and repeat biopsies. Tumor clonality was assessed. Molecular data were compared between men who upgraded and those who did not upgrade to GG ≥2 cancer. RESULTS AND LIMITATIONS: Sixty-six men with median age 64 yr (interquartile range [IQR], 59–69) and prostate-specific antigen 4.9 ng/ml (IQR, 3.3–6.4) underwent repeat sampling of a tracked tumor focus (median interval, 11 mo; IQR, 6–13). IHC-based ERG fusion status was concordant at initial and repeat biopsies in 63 men (95% vs expected 50%, p < 0.001), and RNAseq-based fusion and isoform expression were concordant in nine of 13 (69%) ERG(+) patients, supporting focal resampling. Among 15 men who upgraded with complete data at both time points, integrated DNA/RNAseq analysis provided evidence of shared clonality in at least five cases. Such cases could reflect initial undersampling, but also support the possibility of clonal temporal progression of low-grade cancer. Our assessment was limited by sample size and use of targeted sequencing. CONCLUSIONS: Repeat molecular assessment of low-grade tumors suggests that clonal progression could be one mechanism of upgrading. These data underscore the importance of serial tumor assessment in men pursuing AS of low-grade PCa. PATIENT SUMMARY: We performed targeted rebiopsy and molecular testing of low-grade tumors on active surveillance. Our findings highlight the importance of periodic biopsy as a component of monitoring for cancer upgrading during surveillance.